Chromogranin A regulates gut permeability via the antagonistic actions of its proteolytic peptides. (6th May 2021) - Muntjewerff, Elke M.; Tang, Kechun; Lutter, Lisanne; Christoffersson, Gustaf; Nicolasen, Mara J. T.; Gao, Hong; Katkar, Gajanan D.; Das, Soumita; ter Beest, Martin; Ying, Wei; Ghosh, Pradipta; El Aidy, Sahar; et al.
Abstract: Aim: A "leaky" gut barrier has been implicated in the initiation and progression of a multitude of diseases, for example, inflammatory bowel disease (IBD), irritable bowel syndrome and celiac disease. Here we show how pro‐hormone Chromogranin A (CgA), produced by the enteroendocrine cells, and Catestatin (CST: hCgA352‐372 ), the most abundant CgA‐derived proteolytic peptide, affect the gut barrier. Methods: Colon tissues from region‐specific CST‐knockout (CST‐KO) mice, CgA‐knockout (CgA‐KO) and WT mice were analysed by immunohistochemistry, western blot, ultrastructural and flowcytometry studies. FITC‐dextran assays were used to measure intestinal barrier function. Mice were supplemented with CST or CgA fragment pancreastatin (PST: CgA250‐301 ). The microbial composition of cecum was determined. CgA and CST levels were measured in blood of IBD patients. Results: Plasma levels of CST were elevated in IBD patients. CST‐KO mice displayed (a) elongated tight, adherens junctions and desmosomes similar to IBD patients, (b) elevated expression of Claudin 2, and (c) gut inflammation. Plasma FITC‐dextran measurements showed increased intestinal paracellular permeability in the CST‐KO mice. This correlated with a higher ratio of Firmicutes to Bacteroidetes, a dysbiotic pattern commonly encountered in various diseases. Supplementation of CST‐KO mice with recombinant CST restored paracellular permeability and reversed inflammation, whereas CgA‐KO mice supplementation with CST and/or PST in CgA‐KO mice showed that intestinal paracellular permeability is regulated by the antagonistic roles of these two peptides: CST reduces and PST increases permeability. Conclusion: The pro‐hormone CgA regulates the intestinal paracellular permeability. CST is both necessary and sufficient to reduce permeability and primarily acts by antagonizing PST.